2020
DOI: 10.1002/minf.202000163
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoinformatic Investigation of Medicinal Plants from East Africa

Abstract: Medicinal plants have widely been used in the traditional treatment of ailments and have been proven effective. Their contribution still holds an important place in modern drug discovery due to their chemical, and biological diversities. However, the poor documentation of traditional medicine, in developing African countries for instance, can lead to the loss of knowledge related to such practices. In this study, we present the Eastern Africa Natural Products Database (EANPDB) containing the structural and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 92 publications
0
24
0
Order By: Relevance
“…The database comprises natural drugs from 617 source species and 146 families of plants, animals, bacteria and fungi from Northern and South Africa. It provides rich metadata, literature references and cross-references to major chemical databases that can be easily downloaded and constantly being updated to include data published on newly identified compounds in the Eastern African region [ 35 ]. Interestingly, this database includes compounds with anti-viral (HCV and HIV) activities, and others reported with anti-malarial anti-plasmodial properties.…”
Section: Introductionmentioning
confidence: 99%
“…The database comprises natural drugs from 617 source species and 146 families of plants, animals, bacteria and fungi from Northern and South Africa. It provides rich metadata, literature references and cross-references to major chemical databases that can be easily downloaded and constantly being updated to include data published on newly identified compounds in the Eastern African region [ 35 ]. Interestingly, this database includes compounds with anti-viral (HCV and HIV) activities, and others reported with anti-malarial anti-plasmodial properties.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recent reviews is a compilation of more than 100 public NP databases from different sources that collect more than 400,000 non-redundant molecules [ 18 ]. Among the numerous NP databases in the public domain, there are initiatives to compile NPs from different geographical regions including Africa (e.g., African Natural Products Database—ANPDB) [ 19 ] and Latin America (e.g., Latin American Natural Product Database—LANaPD) [ 20 ] in a single platform.…”
Section: Natural Product Databasesmentioning
confidence: 99%
“…Authors of that work concluded that compounds in BIOFACQUIM are more similar to NuBBE DB and fungi data sets. In a separate and also recent study, Simoben et al reported the drug-likeness of 1870 compounds from the EANPDB database ( Table 1 ) [ 19 ]. It was found that about 85% of the compounds in this database have drug-like features.…”
Section: Chemoinformatic Profilingmentioning
confidence: 99%
See 2 more Smart Citations